2012
DOI: 10.4238/2012.may.22.2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic identification of a wheat (Triticum aestivum)-American dune grass (Leymus mollis) translocation line resistant to stripe rust

Abstract: ABSTRACT. Leymus mollis, a perennial allotetraploid (2n = 4x = 28), known as American dune grass, is a wild relative of wheat that could be useful for cultivar improvement. Shannong0096, developed from interspecific hybridization between common wheat cv. Yannong15 and L. mollis, was analyzed with cytological procedures, genomic in situ hybridization, stripe-rust resistance screening and molecular marker analysis. We found that Shannong0096 has 42 chromosomes in the root-tip cells at mitotic metaphase and 21 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…In this study, we examined the disease resistance of three derivatives with different chromosomes: M47, M42, and M51. In previous studies, several common wheat -L. mollis translocation materials resistant to stripe rust were obtained, which were separately located on wheat chromosomes 2AS, 4AL, 5AS, and 7DL related to L. mollis (Song et al 2008;Bao et al 2012). …”
Section: Source Analysis Of Disease Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we examined the disease resistance of three derivatives with different chromosomes: M47, M42, and M51. In previous studies, several common wheat -L. mollis translocation materials resistant to stripe rust were obtained, which were separately located on wheat chromosomes 2AS, 4AL, 5AS, and 7DL related to L. mollis (Song et al 2008;Bao et al 2012). …”
Section: Source Analysis Of Disease Resistancementioning
confidence: 99%
“…Leymus mollis has been used extensively for hybridization with bread wheat and durum wheat, and numerous useful genes, particularly those for stripe rust resistance and drought stress tolerance, have been successfully transferred into wheat (Anamthawat-Jónsson et al 1997;Zhou et al 2001;Lu et al 2005;Shao et al 2007;Song et al 2008;Wang et al 2008;Wang and Wang 2009;Yang et al 2010;Bao et al 2012;Habora et al 2012). Many derivatives have been produced from Triticum aestivum (common wheat) -L. mollis hybrids, such as octoploid amphiploids, hexaploid amphiploids, and an alien substitution line (Fu et al 1993;Wang et al 2000Wang et al , 2013Forsström and Merker 2001;He et al 2010;Yang et al 2010;Zhao et al 2012;Pang et al 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Using embryo rescue and colchicine treatment, Fu et al (1993) developed different types of octoploid Tritileymus M842 (2n = 56) by successive backcrossing, which exhibited extreme agronomic traits, i.e., long spikes with many florets, big seeds, and tolerance of cold and drought, where Wang et al (2000) indicated that there were two different genome compositions of AABBDDNsNs and AABBDDXmXm according to cytogenetic analysis. Subsequently, several wheat alien germplasms, including addition, substitution, and translocation lines, were obtained by crossing octoploid Tritileymus with wheat cultivars (Fu et al 1996(Fu et al , 1997Bao et al 2012). In order to further exploit and improve the characteristics of octoploid Tritileymus M842, a triple substitution line (05DM6) was generated from the progeny of M842-12 and Triticum durum cv.…”
Section: Introductionmentioning
confidence: 99%
“…(Marais et al, 2009; Kuraparthy et al, 2009; Petersen et al, 2015), Pm40 and Yr50 from Thinopyrum spp. (Luo et al, 2009; Liu et al, 2013), Pm21 from Haynaldia villosa (Chen et al, 1995), YrSn0096 from Leymus mollis (Bao et al, 2012), and Pm2b from Agropyron (Ma et al, 2015). However, rye ( Secale cereal L.) is the most important and valuable related species for the improvement of wheat genetics (Schlegel and Korzun, 1997; Rabinovich, 1998; Lelley et al, 2004; Ren et al, 2012).…”
Section: Introductionmentioning
confidence: 99%